Religious Relations and Economics Hadith Perspective - Masyhari Yanto; Ahmad Mohammad Tidjani (Penerbit Hellow Pustaka, 2024)
This research explores the relationship between religion and economics from an Islamic perspective, focusing on the application of hadith teachings in shaping economic practices and policies. Through a qualitative approach and hermeneutical analysis of relevant hadiths, this research examines the principles of business ethics, prohibited economic practices, production, consumption, and distribution of wealth in Islam. Its findings highlight the emphasis on honesty, transparency, and social responsibility in economic interactions, as well as the prohibition of usury and fraudulent practices. These hadiths also encourage hard work, innovation, moderation in consumption, and prioritizing halal goods. In particular, the obligation of zakat and concern for the mustadhafins (marginalized groups) underline the importance of the redistribution of wealth and social welfare in the Islamic economy. This analysis reveals a strong relationship between religious teachings and economic behavior, with hadith principles influencing individual decisions and societal practices. Furthermore, this research discusses the implications of these teachings for modern economic policy, such as the development of Islamic financial institutions, the integration of zakat in the framework of social policy, and the promotion of business ethics. The relevance of hadith teachings in responding to economic challenges and promoting a more inclusive and sustainable approach was also highlighted. This research contributes to the understanding of the interaction between religion and economics, emphasizing the potential of Islamic principles in shaping a just and prosperous economic system.